Contrast-enhanced ultrasound features of hepatic angiomyolipoma: comparison with AFP-negative and non-viral hepatocellular carcinoma - Zhang, Yafang; Guo, Zhi-xing; Liao, Ying; Yu, Yiwen; Guo, Ruohan; Han, Xu; Lan, Lilong; Zhou, Jianhua (Ultrasound International Open, 2024)
Purpose This study aimed to compare contrast-enhanced ultrasound (CEUS) features of hepatic angiomyolipoma (HAML) and challenging cases of HCC, mainly those with no hepatitis infection but also with a low level of AFP (non-viral AFP- HCC).Materials and Methods The study included pathologically confirmed HAMLs and non-viral AFP- HCCs undergoing CEUS from 2012 to 2023. Sonovue (SV) CEUS and Sonazoid (SZ) CEUS characteristics of the two groups were compared.Results The study included 50 HAMLs (24% on SZ-CEUS) and 88 non-viral AFP- HCCs (21.6% on SZ-CEUS). The CEUS characteristics on SZ-CEUS were similar to those on SV-CEUS to a certain extent. HAMLs more frequently displayed no washout and partial washout with partial no washout, so-called PWNW, in the late phase and post-vascular phase, whereas HCCs more commonly exhibited mild washout. In the post-vascular phase, all non-viral AFP- HCCs exhibited washout, thereby facilitating differentiation from no-washoutHAMLs, superior to SV-CEUS, where some non-viral AFP- HCCs still exhibited no washout in late phase that could not be distinguished from HAMLs. It is noteworthy that PWNW was exclusively found in nodules exhibiting hyper- and hypoechoic separation of the nodules, and hyper- and hypoechoic separation of HAMLs in the post-vascular phase on SZ-CEUS demonstrated PWNW more frequently compared to the late phase, which can potentially help distinguish nodules with hyper- and hypoechoic separation as either HAML or non-viral AFP- HCC. Conclusion: This study highlighted the usefulness of SV- and SZ-CEUS for distinguishing HAML and non-viral AFP- HCC and filled in existing gaps regarding the SZ-CEUS features of HAML.
Keywords: hepatic angiomyolipoma; hepatocellular carcinoma; contrast-enhanced ultrasound; Sonazoid